2023
DOI: 10.1177/10497323231197534
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Lived Experience of Breaking Bad News in Clinical Practice: Five Essentials of a Relational Process

Mattias Tranberg,
Eva M. Brodin

Abstract: The purpose of this study was to develop deeper knowledge about physicians’ lived experiences of breaking bad news by identifying their common meanings and interrelatedness along with their potential alignment with process-oriented and relational aspects. Based on the methodology of descriptive phenomenology, in-depth interviews were conducted with 22 physicians from a wide variety of specialties. The participants were invited to freely reflect upon their experiences of breaking bad news by describing situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Corresponding to previous research, the challenging nature of delivering bad news was highlighted [5,15,35]. A particular challenge when delivering bad news is dealing with the hopes of patients and their relatives [36].…”
Section: Discussionmentioning
confidence: 94%
“…Corresponding to previous research, the challenging nature of delivering bad news was highlighted [5,15,35]. A particular challenge when delivering bad news is dealing with the hopes of patients and their relatives [36].…”
Section: Discussionmentioning
confidence: 94%
“…It could be proposed that patients' perception of their physician as less empathic after receiving bad news is an example of “shooting the messenger,” 2 or that the patient idealizes the physician after having received good news after a period of worry in anticipation of the visit. One explanation for the lower rating following a bad news consultation could be that the physician focuses on the message 18 and, as a result, pays less attention to the patient, which is counterproductive. For the patient, it is as important, if not more important, to be known as it is to know what is ahead.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an Iranian study found, that only 32 (13.6%) of the medical staff had received training in delivering bad news, and a significant majority, 195 (83%), expressed the need for a course to develop this skill (Biazar et al, 2019). This highlights a clear gap in training and underscores the importance of providing further education in this area especially because clinical communication encompasses far more than the mere transmission of information (Bousquet et al, 2015;Matthews et al, 2019;Tranberg and Brodin, 2023).…”
Section: Discussionmentioning
confidence: 99%